Pengaruh Model Pembelajaran Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematika Siswa SMK - Emilianus Jehadus; Ricardus Jundu; Silfanus Jelatu; Aleksander Ecan Gayus (UNIKA SANTU PAULUS RUTENG, 2019)
This study aims to compare the mathematical problem solving abilities of students who use problem solving learning models with direct learning models in the linear program material of the first grade students at SMK Informatika St. Petrus Ruteng in academic year 2018/2019. This research is an experimental research using the design of Posttest-Only Control Design. The population of this research is all students of class X SMK Informatics St. Petrus Ruteng which amounted to 213 people divided into 6 classes with details of the first TKJ 36 people, TKJ II 36 people, TKJ II 36 people, TKJ IV 35 people, TKJ V 35 people and TKJ VI 35 people. Sampling is done by random class. The number of members of the study sample was 71 people. Data on problem solving abilities were collected by a description test. Data were analyzed using t-test calculations with the polled formula variant. Based on the results of data analysis, it was found that the results of t_count = 3.132 and t_table = 1.995 at significant level α = 5% and degrees of freedom = 69. Because t_count> t_table then H_0 is rejected and H_1 is accepted, which means that mathematical problem solving abilities of students using models Problem Solving learning is better than students' mathematical problem solving abilities using direct learning models in linear program material.